2020
DOI: 10.3329/bjch.v43i3.49568
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Menace 2019 Dhaka: A Closer Look

Abstract: Not Available Bangladesh J Child Health 2019; VOL 43 (3) :135-137

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 4 publications
(4 reference statements)
0
11
0
Order By: Relevance
“…Biochemical parameters like albumin and TIBC of this study are significantly and negatively associated with MIS and are in line with most of the studies. 5,23,30,39,54 Malnourished patients had lower serum albumin (an indicator of visceral protein) and creatinine (a marker of muscle mass), and recent research reported that lower serum albumin played a role in the progression of malnutrition among Bangladeshi patients with ESRD. 5 The mean serum albumin (3.5 ± 0.04 g/dl) among HDPs in this study was lower than the recommended 4 g/dl by the National Kidney Foundation Kidney Disease Outcomes Quality Initiative.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Biochemical parameters like albumin and TIBC of this study are significantly and negatively associated with MIS and are in line with most of the studies. 5,23,30,39,54 Malnourished patients had lower serum albumin (an indicator of visceral protein) and creatinine (a marker of muscle mass), and recent research reported that lower serum albumin played a role in the progression of malnutrition among Bangladeshi patients with ESRD. 5 The mean serum albumin (3.5 ± 0.04 g/dl) among HDPs in this study was lower than the recommended 4 g/dl by the National Kidney Foundation Kidney Disease Outcomes Quality Initiative.…”
Section: Discussionmentioning
confidence: 99%
“…1-3 Historically, CKD is highly prevalent in Oceania, Sub-Saharan Africa, Latin America, and Europe, and recently, the burden has been rising in Southeast Asia and Australasia. 1,4 Bangladesh does not have any national data on the prevalence of CKD because of a lack of proper renal registries of the patients 5 ; however, a meta-analysis reported that Bangladesh has a much higher CKD prevalence (22.48%) than the rest of the world mainly in female (25.32%) than the male (20.31%). 6 A recent community-based screening showed the exact CKD prevalence (22.0%) for the rural and peri-urban populations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations